Human Mesenchymal Stem Cell-Derived Exosomal microRNA-143 Promotes Apoptosis and Suppresses Cell Growth in Pancreatic Cancer via Target Gene Regulation - Wang, Bingyi; Xu, Yan; Wei, Yuhua; Lv, Lixin; Liu, Nanbin; Lin, Rui; Wang, Xiuyan; Shi, Baomin (Frontiers in Genetics, 2021)
Background This study aimed to explore the regulatory mechanism of hsa-miR-143-3p and lncRNA RP11-363N22.3–functioning upstream of KRAS–in exosomes derived from human mesenchymal stem cells (hMSCs) in pancreatic cancer. Methods Western blotting and quantitative PCR were used to determine gene expression. In vitro, cell proliferation, apoptosis, and cell cycle and invasion were evaluated using CCK-8 assay, flow cytometry, and transwell assays, respectively. In vivo, the effect of hsa-miR143-3p was investigated using a tumorigenesis test in nude mice. The association between hsa-miR-143-3p and lncRNA RP11-363N22.3 was investigated using the dual-luciferase assay. Results hsa-miR-143-3p expression significantly increased in hMSC exosomes than in those in human pancreatic cancer cell line (CFPAC-1) exosomes. In vitro, compared to the MOCK (CFPAC-1 only) group, cell proliferation and invasion were inhibited and apoptosis was induced in the inhibitor NC (CFPAC-1 + MSC-hsa-miR-3p inhibitor NC) group, while these changes were reversed in the inhibitor (CFPAC-1 + MSC-hsa-miR-3p inhibitor) group. The expression of lncRNA RP11-363N22.3 and genes related to miR-143 significantly decreased in the inhibitor NC group compared to the MOCK group, and increased in the inhibitor group compared to inhibitor NC group. A targeted combinatorial effect was observed between lncRNA RP11-363N22.3 and hsa-miR-143-3p. In vivo, the tumor volume of the mimics (CFPAC-1 + MSC-hsa-miR-143-3p mimics) group was smaller than that of the mimics NC (CFPAC-1 + MSC-hsa-miR-143-3p mimics NC) and MOCK groups. H&E staining showed that there were no obvious pathological changes in MOCK and mimic NC groups, while cell necrosis was seen in some regions in mimic groups. Conclusion hsa-miR-143-3p may promote apoptosis and suppress cell growth and invasion in pancreatic cancer.